MENCARI FORMAT MODEL ORGANISASI YANG TEPAT UNTUK PESANTREN - Muhammad Fathurrahman, Ima Fitriyah dan (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
Pesantren is the oldest Islamic education in Indonesia and attracts a large number of researches. Given that it has developed and transformed itself into various types, generalization is almost impossible to be made. Pesantren is a unique educational institution and organization. This article attempts to examine the organizational model of the pesantren with a focus on its dictintive character. It argued that pesantren is based on a holistic mode of organizational system, which is ‘barākah’. The ‘barākah’ or ‘ngalap barākah’ is an open system that is what distinguishes pesantren from other educational institutions in general. This article also addresses the question on what kind of organizational format that may be best implemented in pesantren.Keywords: Pesantren, Barākah, Organisasi